Analisis Faktor Penyebab Rendahnya Motivasi Belajar Siswa dalam Proses Pembelajaran Matematika di Kelas V SDN 23 Koto Tuo - Oriza Satifa Putri; Safrizal Safrizal; Fadriati Fadriati (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
This study is motivated by what factors cause low student learning motivation in mathematics subjects in class V SDN 23 KotoTuo. The purpose of this study is to describe the factors that cause low student learning motivation in the mathematics learning process in class V SDN 23 Koto Tuo. The type of research used in this study is a case study. The informants in this study were 1 class V elementary school teacher, 20 class V students, who were selected using purposive sampling techniques. The key instrument in this study is the researcher himself, but in the implementation the researcher uses interview guides, cameras, field notes, observations. Data analysis techniques use the stages of data reduction, data display and conclusions. The guarantor of data validity in this study uses triangulation by combining 3 methods of data collection. The results of this study indicate that the factors that cause low student learning motivation in the mathematics learning process of class V SDN 23 Koto Tuo are three, namely: student abilities, student environmental conditions, and teacher procedures in guiding students.